2022
DOI: 10.3390/antiox11050847
|View full text |Cite
|
Sign up to set email alerts
|

NiONP-Induced Oxidative Stress and Mitochondrial Impairment in an In Vitro Pulmonary Vascular Cell Model Mimicking Endothelial Dysfunction

Abstract: The development and use of nanomaterials, especially of nickel oxide nanoparticles (NiONPs), is expected to provide many benefits but also has raised concerns about the potential human health risks. Inhaled NPs are known to exert deleterious cardiovascular side effects, including pulmonary hypertension. Consequently, patients with pulmonary hypertension (PH) could be at increased risk for morbidity. The objective of this study was to compare the toxic effects of NiONPs on human pulmonary artery endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…37,43 Increased ROS generation was observed in BEAS-2B, but not A549, cells exposed to 60 and 100 μg mL −1 NiO NPs for 45 min 31 or 25 and 50 μg Ni mL −1 of NiO NPs for 5 min to 2 h. 19,24 Others found increased ROS, perturbation of the mitochondrial membrane potential, lipid peroxidation, increased tHODE levels, or depletion of antioxidants, such as decreased GSH, SOD, or CAT, in A549 cells exposed to NiO NPs. 30,35,44 NiO NP exposure also caused ROS and nitrite production and mitochondrial impairment in human pulmonary artery endothelial cells HPAEC, 41,45 as well as upregulation of HO-1 in A549 44,46 and 16HBE14o cells. 46 NiO NP exposure also caused cell apoptosis, necrosis, or suppression of cell proliferation in A549, 30,31 H460, 20 HEp-2, 38 BEAS-2B, 24,31,40 HPAEpiC, 40 and HPAEC cells.…”
Section: Cytotoxic Effects Of Nio Nps On Human Lung Cells In Vitromentioning
confidence: 92%
See 2 more Smart Citations
“…37,43 Increased ROS generation was observed in BEAS-2B, but not A549, cells exposed to 60 and 100 μg mL −1 NiO NPs for 45 min 31 or 25 and 50 μg Ni mL −1 of NiO NPs for 5 min to 2 h. 19,24 Others found increased ROS, perturbation of the mitochondrial membrane potential, lipid peroxidation, increased tHODE levels, or depletion of antioxidants, such as decreased GSH, SOD, or CAT, in A549 cells exposed to NiO NPs. 30,35,44 NiO NP exposure also caused ROS and nitrite production and mitochondrial impairment in human pulmonary artery endothelial cells HPAEC, 41,45 as well as upregulation of HO-1 in A549 44,46 and 16HBE14o cells. 46 NiO NP exposure also caused cell apoptosis, necrosis, or suppression of cell proliferation in A549, 30,31 H460, 20 HEp-2, 38 BEAS-2B, 24,31,40 HPAEpiC, 40 and HPAEC cells.…”
Section: Cytotoxic Effects Of Nio Nps On Human Lung Cells In Vitromentioning
confidence: 92%
“…41 Di Bucchianico et al reported that NiO NP-induced BEAS-2B cell apoptosis and necrosis were calcium-dependent, 24 but Duan et al reported that they were via p53 hyperacetylation and Bax activation by downregulation of SIRT1. 39 NiO NP exposure also caused increased cytosolic calcium (Ca 2+ ) concentration in human pulmonary artery endothelial cells HPAEC, 41,45 which was responsible for NiO NP-induced cell apoptosis. Liu et al demonstrated that NiO NP exposure induced apoptosis and ferroptosis in BEAS-2B and HPAEpiC cells via ATF3.…”
Section: Cytotoxic Effects Of Nio Nps On Human Lung Cells In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in intracellular Ca 2+ were detected using Fluo-4 AM green dye (Molecular Probes; Invitrogen Life Technologies, Carlsbad, CA) according to the manufacturer’s protocol (33). Pulmonary microvascular endothelial cells were subjected to different treatments according to the experimental procedures.…”
Section: Methodsmentioning
confidence: 99%